Rooibos flavonoids, orientin and luteolin, stimulate mineralization in human osteoblasts through the Wnt pathway. Issue 3 (14th January 2015) - Nash, Leslie A.; Sullivan, Philip J.; Peters, Sandra J.; Ward, Wendy E.
<x xml:space="preserve">Abstract</x> Scope Several epidemiological studies have shown that tea consumption is associated with higher bone mineral density in women. Flavonoids in tea are recognized as potential estrogen mimics and may positively influence bone metabolism in estrogen‐deficient women. Luteolin and orientin, flavonoids from rooibos tea, are of particular interest as rooibos tea contains no caffeine that can be detrimental to bone health. This study analyzed changes in mineral content when luteolin or orientin was added to a human osteoblast cell line and the potential mechanisms involved. Measurements included alkaline phosphatase (ALP) activity, cell mitochondrial activity, toxicity, and changes in regulatory proteins involved in osteoblast metabolism. Methods and results Mineral was significantly elevated in Saos2 cells treated with orientin (0.1–1.0 μM, 15–100 μM) or luteolin (5.0 μM) and was associated with increased ALP and mitochondrial activity, as determined by the production of p‐nitrophenol and the reduction of 2‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide, respectively. Greater mineral content was also associated with lower toxicity as determined by lactate dehydrogenase activity and lower expression of TNF‐α, IL‐6, sclerostin, osteopontin, and osteoprotegerin. Conclusion Orientin and luteolin, flavonoids in rooibos tea, enhance mineral content in Saos2 cells. These findings provide guidance for doses to be studied in well‐established animal models.